Samotność racjonalisty - Wieczorek, Krzysztof (Filozofia Chrześcijańska, 2015)
The author looks for constitutional elements of human self in order to discover the right relationship between a person and a community, between solitude and dialog. He analyzes different philosophical points of view which either prefer dialogical understanding of human self or the ones which stress human ability of suspension of the contact with the external reality in order to deepen self-understanding. All that leads the author to the analysis of different types of solitude and its value.